2021
DOI: 10.3390/jimaging7050084
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Structure Index (VSI): Retrieving Vegetation Structural Information from Multi-Angular Satellite Remote Sensing

Abstract: Utilization of the Bidirectional Reflectance Distribution Function (BRDF) model parameters obtained from the multi-angular remote sensing is one of the approaches for the retrieval of vegetation structural information. In this research, the potential of multi-angular vegetation indices, formulated by the combination of multi-spectral reflectance from different view angles, for the retrieval of forest above-ground biomass was assessed in the New England region. The multi-angular vegetation indices were generate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…A different spectral index in the latter study showed sensitivity to young leaf flushing as another important structural change (de Moura et al, 2017). Future advances in multi‐angular reflectance products and correction algorithms thus could fill important gaps on the links between phenology and plant community diversity, ecological functioning, and responses to stressors (Hilker et al, 2009; Pacheco‐Labrador et al, 2016; Sharma, 2021). These opportunities have already started to emerge in UAV applications using structure from motion to infer 3‐D structure of landscapes from overlapping images (Dandois & Ellis, 2013); however, phenological analyses using this technique over full‐season time frames are still few (Park et al, 2019).…”
Section: The Potential Of Phenological Remote Sensing To Advance Plan...mentioning
confidence: 99%
See 1 more Smart Citation
“…A different spectral index in the latter study showed sensitivity to young leaf flushing as another important structural change (de Moura et al, 2017). Future advances in multi‐angular reflectance products and correction algorithms thus could fill important gaps on the links between phenology and plant community diversity, ecological functioning, and responses to stressors (Hilker et al, 2009; Pacheco‐Labrador et al, 2016; Sharma, 2021). These opportunities have already started to emerge in UAV applications using structure from motion to infer 3‐D structure of landscapes from overlapping images (Dandois & Ellis, 2013); however, phenological analyses using this technique over full‐season time frames are still few (Park et al, 2019).…”
Section: The Potential Of Phenological Remote Sensing To Advance Plan...mentioning
confidence: 99%
“…et al, 2017). Future advances in multiangular reflectance products and correction algorithms thus could fill important gaps on the links between phenology and plant community diversity, ecological functioning, and responses to stressors (Hilker et al, 2009;Pacheco-Labrador et al, 2016;Sharma, 2021).…”
Section: Phenology-based Indicators Of Vegetation Structurementioning
confidence: 99%
“…The analysis of forest structure changes based on radar or optical data are typically built indices to capture the complexity of the forest structure in terms of both horizontal and vertical structure. For instance, multi-angle remote sensing was used to obtain bidirectional reflectance distribution function (BRDF) model parameters to analyze vegetation structure information [7]. The optical vegetation index has been used as a horizontal structure to examine changes in canopy cover [8,9].…”
Section: Introductionmentioning
confidence: 99%